2004
DOI: 10.1007/s11103-004-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Gamma carbonic anhydrases in plant mitochondria

Abstract: Three genes from Arabidopsis thaliana with high sequence similarity to gamma carbonic anhydrase (gammaCA), a Zn containing enzyme from Methanosarcina thermophila (CAM), were identified and characterized. Evolutionary and structural analyses predict that these genes code for active forms of gammaCA. Phylogenetic analyses reveal that these Arabidopsis gene products cluster together with CAM and related sequences from alpha and gamma proteobacteria, organisms proposed as the mitochondrial endosymbiont ancestor. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
138
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(146 citation statements)
references
References 67 publications
8
138
0
Order By: Relevance
“…3 Based on sequence comparisons, these subunits were initially proposed to be called "ferripyochelin-binding proteins." However, later it became clear that these identifications were based on a falsely annotated data base entry (12). Instead, significant sequence identity was discovered to the prototype ␥-carbonic anhydrase of the Archaebacterium Methanosarcina thermophila (12).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…3 Based on sequence comparisons, these subunits were initially proposed to be called "ferripyochelin-binding proteins." However, later it became clear that these identifications were based on a falsely annotated data base entry (12). Instead, significant sequence identity was discovered to the prototype ␥-carbonic anhydrase of the Archaebacterium Methanosarcina thermophila (12).…”
mentioning
confidence: 99%
“…However, later it became clear that these identifications were based on a falsely annotated data base entry (12). Instead, significant sequence identity was discovered to the prototype ␥-carbonic anhydrase of the Archaebacterium Methanosarcina thermophila (12). Computer modeling using the crystal structure of the archaebacterial ␥-carbonic anhydrase revealed that at least three of the five plant-specific complex I subunits of Arabidopsis have a conserved active site (12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, EST and gene expression analyses based on the full genome have shown that three of eight a-type sequences are expressed in Arabidopsis, whereas all six of the b-type sequences are represented in the EST database (Fabre et al, 2007). In addition, Parisi et al (2004) identified a family of three g-type sequences in Arabidopsis that are all expressed.…”
mentioning
confidence: 99%
“…Similar to S. macrospora, A. thaliana encodes multiple CA isoenzymes that are localized to the cytoplasm, plasma membrane and mitochondria, as well as to chloroplasts (Fabre et al, 2007;Parisi et al, 2004). The major CA of A. thaliana was shown to be the chloroplast-localized AtbCA1 (Ferreira et al, 2008).…”
Section: Cas1 and Cas2 Are Involved In Sordaria Macrospora Fruiting Bmentioning
confidence: 99%